A unique blueschist facies metapelite with Mgrich chloritoid from the Badajoz-Córdoba Unit (SW Iberian Massif): correlation of Late Devonian highpressure belts along the Variscan Orogen - Arenas, R. (2022)
The Badajoz-Córdoba Unit (BCU, SW Iberian Massif) is a Variscan high-P unit mainly constituted by metapelites, metagreywackes, orthogneisses, Grt-amphibolites, and retrogressed eclogites (high-P metamorphism at c. 377 Ma). Discovery of rare metapelites with well-preserved high-P mineral assemblages, including large garnets up to 1 cm in diameter with abundant inclusions, chloritoid (up to XMg = 0.32), kyanite, staurolite, chlorite, phengite (up to Si = 3.16 apfu), paragonite, margarite, and rutile, allows detailed determination of the tectonothermal evolution of the unit. Pseudosection modelling of representative samples indicates that this mineral assemblage formed in blueschist facies (near eclogite facies transition) at P conditions higher than 20 kbar at c. 525°C and that it underwent a subsequent severe exhumation and moderate heating. The lithological composition of the BCU, the age of high-P metamorphism and the characteristics of the high-P mineral assemblages are similar to those found in other high-P and low to intermediate-T units of the Variscan Orogen. All these units form part of a single blueschist-eclogite facies metamorphic belt formed during Late Devonian subduction of the external margin of Gondwana.